Nilai dan Pesan Moral Tarling Menurut Perspektif Pelaku Kesenian Tarling Cirebon: Studi Psikologi Budaya - Rijal Abdillah; koentjoro koentjoro (Psikologika: Jurnal Pemikiran dan Penelitian Psikologi, 2015)
The purposes of this research were to analyze deeply the values and moral message ofTarling in subject perspective ofTarling-Cirebon Art and performers internalization of value and moral message Tarling. The purpose of this research aimed to answer the research question, how a value and moral message according to the subject perspective of Tarling-Cirebon art and performers internalization of value and moral message Tarling? This research is based on an qualitative study. Subjects perspective of value and moral message in Tarling Art were gathered through observations, interviews, and documentation. The analyzing of internalization process of value and moral message was inspired by ethnography. The result of this study indicate that the values of tarling obtained are empathy of subjects in tarling, covering "dandanggula" song ofSunan Kalijaga, "ngalap berkah" or seeking blessing, "a plate of rice" philosophy, "apa jare wong tua ngagem ngageme wong rumah tangga" or happy household, and "payun geneng sabonana payun geneng sabot enteng lakonana" or mutual cooperation. That there is explicitly moral messages that absorbed are "ingsun titip tajug lan fakir miskin" philosophy of Sunan Gunung Djati, conversation in polite language such as "punten" expression, "sabasita" or "unggah-ungguh" behavior, "pamali" or do behavior charily, "yen wis mlatar gage eling" philosophy of tarling, and "saweran"tradition. The internalization process of values and moral messages performers obtained through five stages based on an taxonomy of educational objectives from Bloom, Krathwol, & Masia (1970). The first is an receiving. The second is an responding. The third is that the valuing. The fourth is that organization. The Last internalization process of values and moral messages are the characterization. Keywords: value, moral, tarling cirebon, cultural psychology